PENGARUH KOMPETENSI DAN PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN LAMPUNG TENGAH - H Muh Amir; Ferlison Adi Chandra (Universitas Bandar Lampung (UBL), 2018)
The main problem of the research was, how Performance of employees in the government organizations is not optimal. performance of employees that have an impact organizational performance of employees. The purpose of this study was to determine the influence of competence, and additional employee income toward performance employees finance and asset management agency region central lampung regency. This type of research is descriptive, by taking a sample of 51 employees of the Department of finance and asset management agency region central lampung regency. Research data was collected by observation, documentation and questionnaire distribution and it was analyzed by quantitative method. Primary data process was held by statistical aid, SPSS program version 20, to measure linear regression model. The results showed: (1) competence significant influence toward performance of employees. (2) additional employee income significant influence toward performance of employees. This means that if the additional employee income improved the performance of employees. (3) competence and additional employee income jointly significant influence toward performance of employees of finance and asset management agency region central lampung regency.